Influences of Kelsen in Peru: A Critical Examination - Sobrevilla Alcázar, David (1973)
Hans Kelsen's Pure Theory of Law stands as a cornerstone in the field of legal philosophy, wielding significant influence globally. This paper endeavors to assess the reception and impact of Kelsen's pure theory within the Peruvian legal context. To achieve this objective, the author conducts an analysis of the scholarly contributions of fifteen Peruvian academics from the Pontifical Catholic University of Peru and the National University of San Marcos. Through this examination, the evolution of research in this domain is scrutinized to elucidate both the depth of comprehension regarding Kelsen's theory and the various methodological approaches employed by scholars in critiquing it. The findings underscore a prevailing trend in Peruvian legal philosophy characterized by a primarily expository nature and a notable lack of maturity. It is evident that many critiques of Kelsen's work are grounded in a superficial understanding with his theoretical framework.